Losartan Reduces Trinitrobenzene Sulphonic Acid-Induced Colorectal Fibrosis in Rats - Dov Wengrower; Giuliana Zanninelli; Giovanni Latella; Stefano Necozione; Issa Metanes; Eran Israeli; Joseph Lysy; Mark Pines; Orit Papo; Eran Goldin (Canadian Journal of Gastroenterology)
Intestinal fibrosis – a chronic and progressive process mediated by several factors – occurs in several fibrostenosing enteropathies, but most frequently in patients with Crohn’s disease (CD). Despite the advances made in the understanding of CD and its management over the past 20 years, surgical intervention remains the only treatment strategy for patients with fibrostenosing CD. The results of several studies, however, have suggested that fibrosis may be a reversible and/or preventable phenomenon. Following an overview summarizing the contemporary knowledge regarding the cellular, cytokine and growth factor interactions that contribute to inflammation and the progression of fibrosis, this article describes an experimental animal model of colitis resembling human CD, which the authors used to investigate whether losartan, an angiotensin II receptor antagonist, could be used as a prophylactic agent to reduce the risk of intestinal fibrosis and strictures in patients with CD.